G249(P) Improving Asthma Care in Children and Young People (CYP): Synergy Between Primary and Secondary Care. (24th May 2017) - Bhatt, R; Moreiras, J; Datt, C; Nelson, S; Parr, T; Lakhanpaul, M
Abstract : Aims: A common misconception is that we manage asthma in children well, but, as highlighted in the National Review of Asthma Deaths 1, children are still dying from asthma and the UK has the highest mortality and morbidity in Europe in CYP with asthma 2 . This quality improvement project aims to implement a programme of integration between primary and secondary care by providing update sessions on asthma in primary care with supported asthma clinics for CYP, thus working to standardise and improve the care given. Methods: Asthma Education/update sessions were offered to primary care for two London boroughs between March-July 2016. Pre and post session questionnaires were collected. Alongside the sessions, we offered joint clinics with a senior paediatric trainee and GP, which focused on CYP with asthma or viral induced wheeze. This model builds on the Finland asthma model 3 and the Imperial Hub 4 initiative. Results: Asthma update sessions were delivered in 14 out of 47 practices. 64 clinicians including GPs, pharmacist and practice nurses attended the sessions. 100% of clinicians found the sessions useful and would want them repeated to keep up skills. Results highlighted wide variation in what clinicians included in an asthma review. Post-session clinicians reported being clearer on what should be included in an asthma review and 62% of the clinicians reported learning about new tools that can be used. Twenty four CYP were seen in the joint clinics. None had an asthma action plan or appropriate spacer device, many did not undergo peak flow testing, have a formal diagnosis or appropriate treatment for their severity of asthma with at least 3 of these CYP having been seen recently by secondary care services. The clinics were well received by all patients and clinicians. Conclusion: Improving asthma care requires effective and integrated approach across the health system, and is currently suboptimal. Basic interventions appear to be inconsistently completed by healthcare professionals, likely due to wide variation between individual clinician's approaches and understanding. Positive progress should aim for a standardised approach in management of asthma with improving skills, education and working relationships among all healthcare professionals involved in asthma care.